Advances in Research on Pharmacological Activities and Synthesis of Oleanolic Acid Derivatives at C-3 Position - Zheng, Qutong; Liu, Yi; Chen, Hongfei; Xiao, Yan; Zeng, Xianliang; Wei, Yun; Luo, Xinrui; Xiao, Xuan; Wang, Zongbao; Zheng, Xing (Natural Products Journal, The, 2015)
Oleanolic acid (3β-hydroxyolean-12-en-28-oic acid) belongs to pentacyclic triterpenoid compounds which are widely found in natural plants. Oleanolic acid and its derivatives possess several promising pharmacological activities. The chemical modifications made in the oleanane backbone mainly at carbons C3, C12 and C28 carboxylic acid, have led to a series of new synthetic oleanane triterpenoids. The Oleanolic acid derivatives at C-3 position exhibited the most potent activity. Here, a review of the advances in research on pharmacological activities and synthesis of Oleanolic acid derivatives at C-3 position are presented.
Keywords: oleanolic acid derivatives